Web-Based Chicken Feed Equipment Monitoring System - Sujono Sujono; Lang Elang Timur Demokrat; Primaadi Airlangga (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
The broiler chicken farming industry is a strategic sector in meeting the community's animal protein needs. Feed contributes the largest cost in chicken farming, accounting for approximately 65% of total production costs. Inaccurate feeding can result in suboptimal chicken growth and increased production costs. To address this issue, this research developed a web-based chicken feed weight monitoring system aimed at helping farmers monitor feed availability in real time and analyze feed data more effectively. The system uses a load cell sensor to measure the weight of feed in the feed container and displays the monitoring results online, facilitating user monitoring and decision-making. The initial research phase included analyzing user needs to ensure the system meets field requirements. However, the system still has limitations, such as the lack of environmental sensor integration (temperature and humidity), which are also important for maintaining chicken health, and limited features, including data backup, data download, and mobile display. For further development, the implementation of environmental sensors and these features is expected to improve the system's functionality. This way, farmers can not only accurately monitor feed consumption but also manage coop conditions more comprehensively and gain easy data access through a mobile application, enabling faster and more accurate decision-making.